An electromagnetic strategy to improve the performance of PV panel under partial shading. (March 2021) - Gupta, Ankur Kumar; Maity, Tanmoy; H, Anandakumar; Chauhan, Yogesh Kumar
Abstract: The conventional bypass diodes used in solar photo-voltaic panel have side-effects of forward voltage drop, reduction in efficiency and a few operational problems under partial shading condition. In this work, this bypass diode is replaced by an electromagnetic relay through an efficient alternative approach that consumes less power and offers higher efficiency under partial shading condition of solar module. This approach removes the problems like hotspot formation of the solar cell, open circuit fault under shading condition. A part of this work has been reported and published as an Indian patent. In this extended research work, the different components are designed for the partial shading condition. The hardware setup is developed, and hardware results are compared and validated with the simulated results. The proposed electromagnetic method, with no semiconductor device, works efficiently and effectively under partial shading (low irradiance) scenarios.